(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) can be defined as a series of symptoms related to social interactions, communication, thought patterns, and repetitive behavior, as well as a variable level of intellectual functioning. The existence of a relationship between the use of alcohol and tobacco during gestation, mainly in the first trimester of pregnancy, and the development of ASD in offspring is questioned. This systematic bibliographic review aimed to discuss the relationship between the use of these substances during gestation and the incidence of ASD, describing the mechanisms of action of these legal drugs in the maternal organism and their consequences to the fetus during intrauterine life. This analysis was based on selected articles, amongst scientific publications from the years 2018 to 2023, complete and free, in Portuguese, English, or Spanish, in the PubMed database. Findings in the literature are controversial regarding the relationship between alcohol and tobacco consumption during pregnancy and the incidence of ASD in offspring. However, some studies present mechanisms of action of these drugs that increase the likelihood of ASD development in the intrauterine period, such as exposure to nicotine and formic acid, the production of inflammatory cytokines, and epigenetic changes in fetal tissues. Thus, it is inferred that the use of alcohol and tobacco during pregnancy affects maternal and fetal metabolisms, although there is still little research and evidence regarding its influence on the development of ASD, indicating the need for more incentives for the investigation of this subject.